Manajemen Asuhan Kebidanan Pada Nn. “A” dengan obesitas di SMA Negeri 10 Gowa Tahun 2025 - Afrianisa, Nurul; Firdayanti, Firdayanti; Saleha, Sitti; Alkautzar, Anieq Mumthi’ah; Wahyuningsih, Tri (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2026)
Adolescence is also a transitional age from childhood to adulthood, where at that age many changes are felt by teenagers searching for their identity by following the current trends and lifestyles of the current era. In Indonesia, the prevalence of childhood obesity based on body mass index (BMI/U) and age ratio in children aged 5–12 years increased from 8.8% (Riskesdas, 2013) to 9.2% (Riskesdas, 2018). The prevalence of obesity and overweight among adolescents aged 16 to 18 years also increased from 1.6% to 4.0% and from 5.7% to 9.5%, respectively. Obesity in adolescents is caused by many factors: lack of physical activity, unbalanced diet, excessive intake of macronutrients, frequent consumption of fast food, a history of obesity in parents, and the habit of skipping breakfast.This research paper aims to carry out Midwifery Care Management for Adolescent Ms.